Insufficient funds: Poverty's effect on health - Hartman, Malcolm; Lukich, Alena; Mok, Janice; Sreeram, Padmaja (The Meducator, 2018)
The McMaster Health Forum strives to be a leading hub for improving health outcomes at the regional and provincial levels in Canada. Through problem-solving and discussion, the Forum harnesses information, convenes stakeholders, and prepares action-oriented leaders to meet pressing health issues creatively.